A Boron Dipyrromethene‐Based Fluorescence 'OFF‐ON' Probe for Sensitive and Selective Detection of Palladium(II) Ions and Its Application in Live Cell Imaging. Issue 23 (6th November 2020) - Chen, Xiao‐Fei; Ma, Qinhai; Wang, Zhoulang; Xie, Zeqiang; Song, Yu; Ma, Yanfang; Yang, Zifeng; Zhao, Xin
Abstract: A novel boron dipyrromethene (BODIPY)‐based fluorescent probe BDP−Pd was designed and synthesized. Upon coordination with Pd 2+, the emission of the probe at 508 nm significantly increased, showing an 'OFF‐ON' fluorescence response. The complexation of BDP−Pd with Pd 2+ in both acetonitrile and aqueous solution were then studied by absorption and fluorescence spectra. The binding stoichiometry between the probe and Pd 2+ was found to be 1 : 2, and the binding constant was determined to be 8.5×10 10 M −2 and 8.2×10 10 M −2 in acetonitrile and aqueous solution, respectively. The probe exhibited a detection limit as low as 0.72 ppb toward Pd 2+ with no obvious interference from up to 21 species of common metal ions, suggesting BDP−Pd as a sensitive and selective fluorescent probe for Pd 2+ detection. The fast fluorescence 'OFF‐ON' phenomenon of the probe upon coordination with Pd 2+ ions could be easily observed by a hand‐hold UV lamp under naked eye in solution as well as on homemade test trips. Density functional theory (DFT) calculations were carried out to give the optimized structure of complex BDP−Pd : 2Pd 2+ and rationalize the detection mechanism through a prohibited intramolecular photoinduced electron transfer (PET) process. The bio‐imaging application of the probe was investigated and it showed excellent cell permeability for fluorescent imaging of Pd 2+ ions in A549 human non‐small cell lung cancer cells. Abstract : By employing a photoinduced electron transfer mechanism, a boron dipyrromethene (BODIPY)‐based fluorescence 'OFF‐ON' probe was designed and synthesized which exhibited high sensitivity and selectivity toward Pd 2+ ions in organic solvent, aqueous media and living cells.